2019
DOI: 10.1093/jisesa/iez068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aqueous Extracts from Amazon Plants on Plutella xylostella (Lepidoptera: Plutellidae) and Brevicoryne brassicae (Homoptera: Aphididae) in Laboratory, Semifield, and field trials

Abstract: We evaluated the insecticide activities of aqueous extracts of five species of plants from the Ecuadorian Amazon (Deguelia utilis (ACSm.) AMGAZEVEDO (Leguminosae: Papilionoideae), Xanthosoma purpuratum K. Krause (Alismatales: Araceae), Clibadium sp. (Asteracea: Asterales), Witheringia solanacea L'Hér (Solanales: Solanaceae), and Dieffenbachia costata H. Karst. ex Schott (Alismatales: Araceae)) plus Cymbopogon citratus Stapf. (Poales: Poaceae) under laboratory, open-field conditions in Plutella xylostella L. (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
6
0
3
Order By: Relevance
“…Research [18] showed high concentration of Argemone ochroleuca extract resulted in high mortality of Spodoptera frugiperda larvae even though only a small portion of leaves are consumed. A decrease in feeding rates is a result of feeding deterrent or sublethal toxicity [19]. This implies that insect death is a cause of a combination between starvation and compounds contained in C. gigantea extract.…”
Section: Toxicity Testmentioning
confidence: 99%
“…Research [18] showed high concentration of Argemone ochroleuca extract resulted in high mortality of Spodoptera frugiperda larvae even though only a small portion of leaves are consumed. A decrease in feeding rates is a result of feeding deterrent or sublethal toxicity [19]. This implies that insect death is a cause of a combination between starvation and compounds contained in C. gigantea extract.…”
Section: Toxicity Testmentioning
confidence: 99%
“…They can potentially reduce the use of chemical pesticides and provide new ideas for the synthesis of novel biopesticides for pest control [8,9,11]. Some plant extracts are being used for the management of insect pests such as Plutella xylostella, and Drosophila suzukii, and their application is becoming an integral part of ecological conservation programs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the rest of the world, 139 plant species representing 44 families [ 149 , 153 , 154 , 156 , 166 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ,…”
Section: Resultsunclassified